2001
DOI: 10.2307/3434918
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxicity of Chloroform to Japanese Medaka Fish

Abstract: Materials and Methods Test materials. Chloroform (CAS No. 67-66-3) of 99.8% purity was obtained from Aldrich Chemical Company (Milwaukee, WI). Weekly chemical analyses of aquaria water demonstrated that chloroform did not break down to form other compounds. Under the continuous flow-through dosing regimen, sufficient chloroform remained in solution during testing to maintain dosage levels. Approximately 10 L of 100 mg/L chloroform stock were prepared each day. Processed well water was the diluent used. The chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…Darnerud et al (1989) showed the presence of nonvolatile metabolites of carbon-14-labeled 1,2-dibromoethane and CHCl 3 mainly in liver and kidney of rainbow trout and, to lesser extent, in gill and intestinal mucosa. The hepatic bioaccumulation of BrCHCl 2 occurring with chronic exposure in medaka (Oryzias latipes) was dependent on body levels (Toussaint et al 2001a), but apparently CHCl 3 is not bioaccumulated in liver (Toussaint et al 2001b). Both previous and present results suggest that HM metabolism depends on the species involved as well as on patterns of chlorination (Birge and Cassidy 1983) and body levels (Hendriks 1995).…”
Section: Biomarkers Of Exposure and Hm-induced Damagementioning
confidence: 48%
See 1 more Smart Citation
“…Darnerud et al (1989) showed the presence of nonvolatile metabolites of carbon-14-labeled 1,2-dibromoethane and CHCl 3 mainly in liver and kidney of rainbow trout and, to lesser extent, in gill and intestinal mucosa. The hepatic bioaccumulation of BrCHCl 2 occurring with chronic exposure in medaka (Oryzias latipes) was dependent on body levels (Toussaint et al 2001a), but apparently CHCl 3 is not bioaccumulated in liver (Toussaint et al 2001b). Both previous and present results suggest that HM metabolism depends on the species involved as well as on patterns of chlorination (Birge and Cassidy 1983) and body levels (Hendriks 1995).…”
Section: Biomarkers Of Exposure and Hm-induced Damagementioning
confidence: 48%
“…Dependency of the patterns of HM halogenation on sex-linked response may nevertheless exist. Chronic exposure to CHCl 3 induced biliary carcinogenesis in female medaka, but early hepatocellular necrosis and concomitant compensatory hyperplasia did not occur (Toussaint et al 2001b). Although a histopathological study of C. riojai was not made, the greater HSI values obtained in summer may be associated with canalicular cholestasis and hyperplasias.…”
Section: Biomarkers Of Exposure and Hm-induced Damagementioning
confidence: 94%
“…The exposure of Oreochromis niloticus Thiobencarp herbicide for 8 weeks revealed that, fish showed a reduction in body weight gain compared to the control group parameters such as specific growth rate (SGR), food conversion efficiency (FCE), protein efficiency ratio (PER), food conversion rate (FCR) decreased with increased concentration of mercuric chloride. Decrease growth rate as observed by Toussain et al [32] and Onusiriuka, [33] that exposed Japanese Medaka fish and…”
Section: Growth Parametersmentioning
confidence: 62%
“…Studies from this and other laboratories have shown that hepatocytes and biliary epithelial cells are sensitive responders under conditions of acute and chronic toxicity in medaka (Toussaint et al, 2001a, 2001b; Wolf and Wolfe 2005; Hardman et al, 2008; Volz et al, 2008). The role of BPDECs in the hepatobiliary toxicity after exposure to GW4064 required use of a tiered histopathological approach.…”
Section: Discussionmentioning
confidence: 76%